A modest step towards fixed parities - OSSOLA, R. (PSL Quarterly Review, 2013)
Many authors welcomed the shift to floating exchange rates as they expected it to result in lower inflation, unemployment and balance of payments disequilibria. However, the new system exhibits two sharp daily fluctuations of exchange rates, imposing unwelcome risks on enterprises. Thus, the urge towards more stable exchange rates is becoming intense. The paper analyses the gradual stabilisation of exchange rates through the establishment of monetary zones. JEL: F32, E31, F33